New technologies to guarantee physical well-being: Didactic and motivational strategies - Raffaele Di Fuccio; Dario Lombardi; Francesca Finestrone (Pensa MultiMedia, 2022)
The introductory part of this paper will discuss the importance of the use of new technologies, analysing their typologies and benefits, in the context of prevention and treatment of chronic and degenerative diseases, with the aim of guaranteeing physical well-being and the consequent improvement of the quality of life in modern society. In the second section, the contribution, using a narrative theoretical method, will deal with the methodologies applied in the pursuit of the aforementioned aim. In the final section, the benefits found in the population will be highlighted, underlining how the link between new technologies and physical well-being will make them inextricably complementary in the future.